Availability, Community Of Practice And Relative Advantage Of ICT Resources Utilisation In Teaching–Learning Secondary School Agriculture: Lessons From Swaziland - Mndzebele, Nomsa; Dludlu, Mzomba; Mndebele, Comfort B.S. (Advances in Social Sciences Research Journal, 2018)
Culture and society practices must adjust to changing challenges impacting the education sector with the advent of ICTs. The study determined the extent of availability and community of practice in respect of ICT resources. Furthermore, it described the perceptions of respondent secondary Agriculture teachers regarding the relative advantage of ICT tools in teaching and learning in the Southern African country (Swaziland) experience. A descriptive survey approach of data collection and analysis was employed. Findings revealed that ICT tools are somewhat adequately available for utilisation and integration in teaching agriculture. This comes the importance of the same. Availability of reliable adequate Internet remains a big challenge. Electricity and road networks are available and reliable. Community of practice in the ICT context is also low and problematic. Respondents experience ease of ICT use and less complexity in usage. It is recommended that: 1) ICT school policies be put in place and made mandatory; 2) Foster partnership with State-Owned Enterprises responsible for ICT Internet layout to negotiate reduced cost of installation; 3) Professional development workshops should be introduced with some incentives to enhance community of practice and popularise ICT utilisation and integration.